The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jpca.9b01189
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Modeling of the Structure and H Bonding in Triethanolammonium-Based Protic Ionic Liquids with Sulfonic Acids

Abstract: The results of electronic structure calculations based on density functional theory (DFT) for protic ionic liquids (PILs) consisting of triethanolammonium cation paired with anion of different sulfonic acids are reported. The influence of the anion nature on the structure and interactions in the ion pairs that are formed in these PILs is discussed in detail. Multiple H-bonding interactions exist between the protons in the NH/OH groups of the cation and different oxygen atoms of the acid anion in the ion pairs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…[64][65][66] The B3LYP functional and Grimme's dispersion has been applied successfully and extensively used to study the structure and intermolecular interactions in the protic ionic liquids. 49,52,65,67,68 The cartesian coordinates of all the optimized structures along with their energy values were provided in the ESI. † COSMO-RS calculations.…”
Section: Analysis and Characterization Methodsmentioning
confidence: 99%
“…[64][65][66] The B3LYP functional and Grimme's dispersion has been applied successfully and extensively used to study the structure and intermolecular interactions in the protic ionic liquids. 49,52,65,67,68 The cartesian coordinates of all the optimized structures along with their energy values were provided in the ESI. † COSMO-RS calculations.…”
Section: Analysis and Characterization Methodsmentioning
confidence: 99%
“…23 We have recently shown that additional hydrogen bonds between three OH protons of triethanolammonium cation and oxygen atoms of different anions in the ion pairs lead to higher interaction energy and formation of energetically more stable ion pairs in comparison with those with a TEA cation. 32 For triethanolammonium PILs with a number of anions, a correlation between their melting temperatures and calculated cation−anion interaction energies has been obtained; namely, it has been found that an increase in this energy in the series of the studied ion pairs leads to higher melting temperature of the PILs. Besides, in ref 33, for PILs based on trifluoroacetate anion and different alkylammonium (diethyl-, dimethylethyl-, tributyl-, diisopropylethyl-) cations, it has been found that higher interaction energy between the cation and anion in the hydrogen bonded ion pair obtained by quantum-chemical calculations results in lower ionicity of the corresponding PILs.…”
Section: ■ Introductionmentioning
confidence: 91%
“…For primary alkylammonium-based PILs, there is a significant change in hydrogen bonding interactions ranging from short and linear to long and bi/trifurcated and it reflects their macroscopic properties . We have recently shown that additional hydrogen bonds between three OH protons of triethanolammonium cation and oxygen atoms of different anions in the ion pairs lead to higher interaction energy and formation of energetically more stable ion pairs in comparison with those with a TEA cation . For triethanolammonium PILs with a number of anions, a correlation between their melting temperatures and calculated cation–anion interaction energies has been obtained; namely, it has been found that an increase in this energy in the series of the studied ion pairs leads to higher melting temperature of the PILs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of works now aim at studying the structure and interionic interactions in tertiary alkylammonium PILs. ,,, The tertiary cation in these cases demonstrates a marked ability to act as a proton donor (due to a single N–H site) and to form one strong and directional hydrogen bond with the acid anion. In our earlier DFT studies, we obtained numerous correlations between the quantum chemical calculations of the ion pairs with a tertiary cation and experimental data on the physicochemical properties of the corresponding PILs. Furthermore, all these studies indicated that the magnitude of the interaction energies of the ion pairs of the triethylammonium class of PILs was significantly lower than that for the PILs with a triethanolammonium cation, which in turn led to the increase in the viscosity and decrease in the electric conductivity of the latter. , The H-bonding interaction in the ion pairs of triethylammonium-based PILs with different anions tended to become stronger with the increase in the anion proton affinity .…”
Section: Introductionmentioning
confidence: 99%